(untitled) (Journal of Partial Differential Equations, 1997)
In this paper, the existence of travelling wave solution for nonlinear equation wiili non local advection ρ∂∂t(u^mm) = ∂²u∂x²-∂∂x[φ(k∗u)u]+u^nf(u) is studied in the case of m ≥ 1, n ≥ 1. When ε,φ, f, m and n satisfy some determinate conditions, there exists the travelling wave solution.